PERAN PLENO KAMAR AGAMA MAHKAMAH AGUNG DALAM MENCAPAI TUJUAN PERUNDANG-UNDANGAN KELUARGA INDONESIA - khiyaroh, khiyaroh (Ahkam: Jurnal Hukum Islam, 2020)
The Plenary Meeting of the Supreme Court is a system established to maintain the unity of the application of the law and the consistency of the judge's decision. This system is carried out every year and starts in 2011. In the plenary meeting of the Supreme Court there is a division of rooms according to the abilities of each judge divided into five rooms. Namely the criminal chamber, civil chamber, state administration room, religious chamber, and military room. In the case of the plenary chambers of religion there are a number of things that are regulated every year and there are some rules that have been reformulated. With the existence of the plenary chamber of the Supreme Court of Religion, the rules in it partly reflect the purpose of family law legislation. But there are rules that are actually on the contrary to the goals of family law legislation. This paper aims to find out how the role of SEMA as a result of the Plenary Meeting of the Supreme Court of the Supreme Court has been in accordance with the objectives of Law No.1 of 1974 concerning marriage. This research is a library research with a juridical approach by looking at the legal rules and legal principles, and is analytic descriptive. The results obtained are the rules in the SEMA as the results of the plenary meeting of religious chambers are not all in line with the objectives of the Indonesian marriage law. Keywords: Supreme Court, Plenary Chamber, Purpose of Family Law.